A general approach to determine texture patterns using pole figure - Junwei Fu (Journal of Materials Research and Technology, 2021)
In the present work, a general and simple approach to determine texture patterns using pole figure was developed. For the rolled materials, the rolling plane can be determined by the ratio of OP/R in the given pole figure. Here, OP is the length from the center to an arbitrary pole in the pole figure, and R is the radius of the projection circle in the pole figure. Rolling direction for the rolled materials or the extrusion direction for the extruded materials can be directly calculated using the coordinate values of the poles in the given pole figure. For cubic and hexagonal materials, the calculated results using the developed approach are in agreement with the standard stereographic projection pole figures. The textures in the rolled and annealed Fe–17Cr ferritic stainless steel and extruded Mg–2Mn alloy were examined by electron backscatter diffraction and X-ray diffraction. The proposed approach was applied to determine texture patterns in the above two materials. It was found that {111}<112> type of γ-fiber texture develops for the as-annealed Fe–17Cr ferritic stainless steel and <0001> + <10−10> double fiber texture develops for the extruded Mg–2Mn alloy.